2020
DOI: 10.1186/s12967-020-02293-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal mixed adenoneuroendocrine carcinoma: a population level analysis of epidemiological trends

Abstract: Background The rise in incidence and mortality of gastrointestinal mixed adenoneuroendocrine carcinoma (MANEC) has not been well focused. The aim of our study was to examine epidemiological trends in incidence and incidence-based (IB) mortality of gastrointestinal MANEC at a population level. Methods The incidence and IB mortality of gastrointestinal MANEC as well as data on affected patients from 2000 to 2016 were obtained from the Surveillance, Epidemiology, and End Results database. Trends in incidence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
1
23
0
1
Order By: Relevance
“…Patients with distant MiNENs had the worst prognosis, with 5-year OS and CSM rates of 12.3 and 78.6%, respectively. One study found that metastatic gastrointestinal MiNENs had a higher incidence than localized disease (22). In our study, the proportion of patients with an advanced stage MiNENs was approximately 33% and this proportion was even higher in other studies (23,24).…”
Section: Discussionsupporting
confidence: 39%
“…Patients with distant MiNENs had the worst prognosis, with 5-year OS and CSM rates of 12.3 and 78.6%, respectively. One study found that metastatic gastrointestinal MiNENs had a higher incidence than localized disease (22). In our study, the proportion of patients with an advanced stage MiNENs was approximately 33% and this proportion was even higher in other studies (23,24).…”
Section: Discussionsupporting
confidence: 39%
“…Gastrointestinal (GI) tumors are one of the most serious health complications in the world. They mainly include seven major cancers: liver hepatocellular carcinoma, stomach adenocarcinoma, esophageal carcinoma, pancreatic adenocarcinoma, colon adenocarcinoma, cholangiocarcinoma, and rectum adenocarcinoma [ 18 ]. Understanding the molecular markers that predict prognosis of GI tumors can guide clinical management of patients with these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Since the colon biopsy in our patient was predominantly large cell neuroendocrine carcinoma, which is notorious for its aggressiveness and high metastatic potential [ 20 ], it is very likely to be the culprit of the hepatic lesions, although no biopsy was collected from the liver to confirm this. Wang et al demonstrated a relationship between the size of the primary tumor and the presence of metastatic lesions, regardless of whether the metastasis is to lymph nodes or to distant organs, with primary tumors of more than 2 cm being 2 times more likely to have metastatic lesions [ 25 ].…”
Section: Discussionmentioning
confidence: 99%